Promoting pulp and paper mill material circularity: functionalised organic-inorganic cellulosic mulch films - Du Toit, Jacobus Christiaan Faure (Stellenbosch : Stellenbosch University, 2026)
Thesis (MEng)--Stellenbosch University, 2026.